2014
DOI: 10.1186/ar4431
|View full text |Cite
|
Sign up to set email alerts
|

Patients with rheumatoid arthritis in clinical remission and ultrasound-defined active synovitis exhibit higher disease activity and increased serum levels of angiogenic biomarkers

Abstract: IntroductionThe aim of this study was to identify and characterize subclinical synovitis in patients with rheumatoid arthritis (RA) in clinical remission using power Doppler ultrasound (PDUS) and serum levels of biomarkers of inflammation and/or angiogenesis.MethodsWe selected patients with RA in clinical remission defined as a Disease activity score of 28 joints (DAS28)-erythrocyte sedimentation rate (ESR) <2.6 for more than six months tested by two independent rheumatologists. Clinical, epidemiological, demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 26 publications
9
44
0
6
Order By: Relevance
“…Inoue et al found DAS28-CRP 2.3 matched DAS28-ESR remission in Japanese patients [10].The present study suggests that composite scores overestimate remission and patients retain subclinical inflammation found on MRI. Our results join the various studies that have proven the dissociation between clinical remission according different composite scores and remission in imaging either by ultrasound (Ramirez J et al [11]) or MRI (Gandjbakhch F et al [12]) or both (Foltz V et al [13]). …”
Section: M6 P Referencessupporting
confidence: 58%
See 2 more Smart Citations
“…Inoue et al found DAS28-CRP 2.3 matched DAS28-ESR remission in Japanese patients [10].The present study suggests that composite scores overestimate remission and patients retain subclinical inflammation found on MRI. Our results join the various studies that have proven the dissociation between clinical remission according different composite scores and remission in imaging either by ultrasound (Ramirez J et al [11]) or MRI (Gandjbakhch F et al [12]) or both (Foltz V et al [13]). …”
Section: M6 P Referencessupporting
confidence: 58%
“…With recent improvements in the treatment of rheumatoid arthritis, remission has become an achievable goal for a large proportion of RA patients, and remission is now a defined target in current RA guidelines. However, there is concern about whether current criteria reflect true remission characterized by the abrogation of synovitis and consequently, a lack of radiographic progression [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramirez и соавт. [19] изучали субклинический сино-вит у пациентов с РА в клинической ремиссии с помощью УЗИ и уровней сывороточных биомаркеров воспаления и ангиогенеза. Пациенты с активным синовитом (45,4% от общего числа включенных пациентов) имели более высокие показатели DAS28-СРБ, DAS28-СОЭ, SDAI, и только 12% из них принимали глюкокортикоиды (≤5 мг/сут), по срав-нению с 40% пациентов без активного синовита (р=0,044).…”
Section: таблицаunclassified
“…В исследовании J. Ramires и соавт. [19] у 55 пациентов с длительно текущим РА, находившихся в клинической ре-миссии, отмечена корреляция между активностью субкли-нического синовита по данным ЭД, значениями DAS28-СРБ, DAS28-СОЭ, SDAI и уровнем проангиогенных био-маркеров, таких как MMП2, ТФРβ1 и ANG. При этом кор-реляции между УЗ-признаками синовита и концентрацией провоспалительных цитокинов (ФНОα, ИЛ6, ИЛ8, ИЛ17A, ИЛ17F, ИЛ18, ИЛ20, ИЛ23 и ИЛ33) также не отме-чено.…”
unclassified